(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Scientific achievements of researchers, who have studied the problem of ability to handle stress in various fields, which made it possible to set definitions, are analyzed in the article: stress – as a special reaction of the body to extrinsic stimuli; the ability to handle stress – as a personal characteristic of resistance to negative factors; and the key definition is withdrawn – the professional pilots ability to handle stress – the personal characteristic which gives the aviation specialist an ability to adapt and be emotionally stable under the influence of stressors and maintain high efficiency during working practice. It is pointed out that different types of occupational stress, such as informational, emotional and communicative stress have been differentiated. As for the professional activity of aviation specialists, the following negative factors are singled out: high neurotic-emotional tension; unusual spatial orientation; imposed work speed and lack of time; the presence of unusual professional conditions of activity, which include such as noise, aircraft chatter vibration and acceleration state during performing various maneuvers; the advantage of brain work and almost complete absence of physical effort, the presence of hypomobility and physical inactivation, etc. 228 The specific of the work of pilots lies in the special conditions of activity. In different modes of the technological process, the pilot performs his functions in the system, where control is carried out by automatic air navigation systems. The specific of the work of pilots is determined in a number of ways: 1) high speed of technological process development; 2) processing large amounts of information in a short period of time; 3) the sense of responsibility and the cost of error in working practice; 4) the rapid transition from waiting period to strenuous work; 5) the intensity of work; 6) the rapid change of meteorological conditions; 7) negotiation monotonous noise factors; 8) the constancy of visual images while observing a cloudy sky, flying in complex ones. Summing up what has been said, aviation workers belong to the category of people with a high level of occupational stress. There are main indicators of psychological readiness to perform professional tasks under stress such as adaptive abilities to stress, professional reliability and the ability to handle stress. Therefore, the formed ability to handle stress ensures the successful performance of professional duties, maintains high efficiency during the action of stress factors, which is an important condition for the professional activity of aviation professionals. In contrast, undeveloped ability to handle stress is characterized by an inability to perform professional duties in extreme situations, which can lead to both health problems and negative consequences in professional occupation.